DIGESTING FOLKTALES FOR LANGUAGE TEACHING - Sobirova Feruza Mahamatismayilovna (Web of Journals Publishing, 2025)
This paper explores how folktales can be “digested” – systematically analyzed and adapted – to serve as effective tools in English language teaching (ELT). Drawing on narrative theory, cultural studies, and second language acquisition (SLA) research, it argues that folktales provide rich linguistic input, cultural knowledge, and motivational value. The paper proposes practical strategies for integrating folktales into EFL classrooms, supporting vocabulary development, listening comprehension, and intercultural competence.
Keywords: Folktales, Language Teaching, Narrative Techniques, EFL, Cultural Competence.